2013
DOI: 10.1620/tjem.229.1
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Anemia Following Posterior Decompression Surgery for Lumbar Spinal Canal Stenosis

Abstract: The incidence of lumbar spinal canal stenosis (LSCS) is increasing in Japan. Posterior lumbar decompression surgery, wide fenestration and laminectomy, for LSCS is a common treatment modality. Compared with posterior fusion surgery, posterior decompression surgery has been considered as less invasive. However, no reports regarding postoperative anemia following posterior decompression surgery have been published. In this retrospective study, we evaluated changes in hemoglobin values following wide fenestration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
0
1
Order By: Relevance
“…An earlier study involving patients undergoing posterior lumbar decompression surgery observed a mean drop in hemoglobin of 2.4 g % from 13.6 g% before surgery to 11.2 g % after surgery. 18 In contrast, the mean change in hemoglobin before and after surgery in our study was only 1 g% in our study. This minimal difference in pre- and postoperative hemoglobin values along with lower incidence of postoperative anemia compared to previous studies in non-neurosurgical population, suggests good intraoperative blood transfusion practices in our hospital.…”
Section: Discussioncontrasting
confidence: 77%
“…An earlier study involving patients undergoing posterior lumbar decompression surgery observed a mean drop in hemoglobin of 2.4 g % from 13.6 g% before surgery to 11.2 g % after surgery. 18 In contrast, the mean change in hemoglobin before and after surgery in our study was only 1 g% in our study. This minimal difference in pre- and postoperative hemoglobin values along with lower incidence of postoperative anemia compared to previous studies in non-neurosurgical population, suggests good intraoperative blood transfusion practices in our hospital.…”
Section: Discussioncontrasting
confidence: 77%